Characteristics of Carbon from Oil Palm Shell Activated by Low Concentration of Zinc Chloride Activator - Joko Sulistyo; Purnama Darmadji; Sri Nugroho Marsoem (Masyarakat Peneliti Kayu Indonesia, 2014)
Currently, a large amount of oil palm shell has been dumped as waste from palm oil processing in Indonesia. Using a low concentration of zinc chloride (ZnCl2), thermal treatment during pre-carbonization was applied in the preparation of activated carbon from oil palm shells at various temperatures and reaction durations. This study, therefore, aims to investigate the physical and chemical characteristics of activated carbon prepared. Oil palm shells collected from a plantation in Palembang were carbonized by two methods, one-stage carbonization (at 300°C for 3 hours) and two-stage carbonization (at 300°C for 3 hours, then at 600°C for an hour) before chemical activation using ZnCl2, at a concentration of 10 and 15%wt. Activation of oil palm shell charcoal was conducted at 600, 700, and 800°C and reaction times of 60, 120, and 180 minutes. The results showed two-stage carbonization, high temperature, and prolonged reaction time is bound to increase burn-off as well as methylene blue adsorption, and decrease the yield and volatile matter content of the activated carbon prepared. Meanwhile, high ZnCl2 concentration increased the ash content and the methylene blue adsorption. In addition, the two-stage carbonization had higher iodine adsorption compared to the one-stage carbonization. The activated carbon with high iodine (769.3 mg/g) and methylene blue adsorption (133.7 mL/g) levels was obtained by two-stage carbonization using 15%wt ZnCl2 at a temperature and reaction time of 800°C and 180 minutes, respectively.